2018
DOI: 10.1111/1346-8138.14597
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal relationship between herpes zoster and cardiovascular diseases: A nationwide population‐based case–control study in Korea

Abstract: Recently, herpes zoster (HZ) has been identified as a risk factor for stroke, but there have been few studies on the relationship between HZ and other cardiovascular diseases (CVD), including myocardial infarction (MI) and heart failure (HF). The purpose of this study was to investigate the risk of HZ occurrence after CVD and the occurrence of CVD after HZ. This was a retrospective case-control study based on the National Health Insurance System claims database for 20 311 patients with HZ and 13 980 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
(56 reference statements)
0
16
0
Order By: Relevance
“…Text headings and medical subject heading (MeSH) terms used in the searches included HZ, shingles, HZO, stroke, TIA, cerebrovascular disease, and MI. Fifteen studies examined the associations between unspecified HZ types and the following: Non-specified stroke [2,3,4,5,6,7,8,9], ischemic stroke [7,10,11], hemorrhagic stroke [7], transient ischemic attack (TIA), a composite of stroke and TIA [12,13], myocardial infarction (MI) [2,5,9,10,11], acute coronary syndromes (MI and unstable angina) [14], and incident coronary artery disease, including angina and MI (Table 1, Table 2) [15]. There were also eight studies regarding HZO and cardiovascular disease (CVD), five studies of non-specified stroke [2,3,6,7,16], and studies with ischemic stroke [10], hemorrhagic stroke [7], and MI [10] as endpoints (Table 3).…”
Section: Studies Investigating the Association Between Hz And Cvd mentioning
confidence: 99%
See 3 more Smart Citations
“…Text headings and medical subject heading (MeSH) terms used in the searches included HZ, shingles, HZO, stroke, TIA, cerebrovascular disease, and MI. Fifteen studies examined the associations between unspecified HZ types and the following: Non-specified stroke [2,3,4,5,6,7,8,9], ischemic stroke [7,10,11], hemorrhagic stroke [7], transient ischemic attack (TIA), a composite of stroke and TIA [12,13], myocardial infarction (MI) [2,5,9,10,11], acute coronary syndromes (MI and unstable angina) [14], and incident coronary artery disease, including angina and MI (Table 1, Table 2) [15]. There were also eight studies regarding HZO and cardiovascular disease (CVD), five studies of non-specified stroke [2,3,6,7,16], and studies with ischemic stroke [10], hemorrhagic stroke [7], and MI [10] as endpoints (Table 3).…”
Section: Studies Investigating the Association Between Hz And Cvd mentioning
confidence: 99%
“…Recent epidemiological studies ( n = 15) from Asia (Taiwan [3,14,15,16] and Korea [9,11,12]), Iran [8], Europe (the United Kingdom [2,6], Germany [7], Demark [13], and Sweden [4]), and the United States [5,10] showed an increased incidence of stroke or MI in patients with a recent history of zoster. The characteristics of the 15 studies are displayed in Table 1, Table 2 and Table 3.…”
Section: Herpes Zoster and Risk Of Stroke Or Myocardial Infarctionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one case-control study in Korea, Seo et al showed a significant increased risk of severe HZ requiring hospitalization in ischemic stroke. However, no studies have linked the risk of HZ occurrence to hemorrhagic stroke [21]. Therefore, the aim of this study was to survey whether HZ risk is higher in persons with stroke compared to the general population and the relevance to different type of stroke.…”
Section: Introductionmentioning
confidence: 99%